Could Globalisation be Good for World Health? - Thomas Pogge (Global justice: Theory, Practice, Rhetoric, 2008)
Every day thousands of people die from poverty-related causes. Many of these deaths could be avoided if appropriate medical treatments were available to the world’s poor. Due to the current tructure of the international patent regime, they are not. Since the risks and costs associated with pharmaceutical innovation are extremely high, to incentivise research, inventor firms are granted a temporary monopoly over newly invented drugs. While allowing firms to make up for the costs of research, this has the morally perverse effect of raising the prices of pharmaceuticals to a level where they become unaffordable to the world’s poor. To correct this grievous flaw, the paper proposes a concrete and realistic alternative scheme which, by rewarding medical innovators in proportion to the impact of their drugs on the global disease burden, would incentivise the production and selling of crucial drugs for the world’s poor at prices accessible to them.